Hutchinson Dictionary of World Mythology - Publishing, Helicon (Helicon Publishing, 2005)
Authoritative reference guide to the major characters and themes of mythology from around the world.
Keywords: Electronic books. -- local; Folklore -- Dictionaries; Mythology -- Dictionaries